Structural biology of DOCK‐family guanine nucleotide exchange factors. Issue 6 (4th November 2022) - Boland, Andreas; Côté, Jean‐Francois; Barford, David
Abstract : DOCK proteins are a family of multi‐domain guanine nucleotide exchange factors (GEFs) that activate the RHO GTPases CDC42 and RAC1, thereby regulating several RHO GTPase‐dependent cellular processes. DOCK proteins are characterized by the catalytic DHR2 domain (DOCK DHR2 ), and a phosphatidylinositol(3, 4, 5)P3 ‐binding DHR1 domain (DOCK DHR1 ) that targets DOCK proteins to plasma membranes. DOCK‐family GEFs are divided into four subfamilies (A to D) differing in their specificities for CDC42 and RAC1, and the composition of accessory signalling domains. Additionally, the DOCK‐A and DOCK‐B subfamilies are constitutively associated with ELMO proteins that auto‐inhibit DOCK GEF activity. We review structural studies that have provided mechanistic insights into DOCK‐protein functions. These studies revealed how a conserved nucleotide sensor in DOCK DHR2 catalyses nucleotide exchange, the basis for how different DOCK proteins activate specifically CDC42 and RAC1, and sometimes both, and how up‐stream regulators relieve the ELMO‐mediated auto‐inhibition. We conclude by presenting a model for full‐length DOCK9 of the DOCK‐D subfamily. The involvement of DOCK GEFs in a range of diseases highlights the importance of gaining structural insights into these proteins to better understand and specifically target them. Abstract : This review discusses structural studies that have provided mechanistic insights into the function of DOCK guanine nucleotide exchange factors (GEFs). Representative structures of members of the DOCK family of GEFs in complex with their cognate Rho GTPases are shown (read the review for more details).